"Going through a little bit of growing pains": A qualitative study of the factors that influence the route choice of regular bicyclists in a developing cycling city. (August 2021) - Desjardins, Elise; Apatu, Emma; Razavi, S. Donya; Higgins, Christopher D.; Scott, Darren M.; Páez, Antonio
Highlights: Route choice is influenced by infrastructure and streetscape. Bicycling is perceived to be excluded from roads through policy and design. Regular bicyclists have mixed perceptions of existing infrastructure. Infrastructure changes should be more aligned with stronger policy changes. Bicycling uptake may be hindered if it is not more explicitly accommodated. Abstract: As cities make concerted efforts to become more bicycle-friendly through policy changes and infrastructure, it is important that such efforts ultimately support people who currently bicycle and remove barriers that may prevent more people from bicycling. Travel surveys can reveal the nature and distribution of bicycling trips, but perceptions and behaviours of bicyclists are better understood through qualitative methods. In particular, developing cycling cities are unique settings to examine how the built environment supports bicycling as changes are made to increase bicycling levels. Through semi-structured interviews, this research explores the case of Hamilton, Ontario and the factors that influence route choice from the perspective of regular bicyclists. Major themes were identified using thematic analysis: (i) exclusion from road space; (ii) infrastructure; and (iii) streetscape. Bicyclists highly value infrastructure and seek routes that minimize interactions with cars, while avoiding many arterial roads that prioritize motorists. Routes that appear to be more human-oriented or that have nature are also attractive. Many regular bicyclists report that current bicycle infrastructure does not meet their preferences. Despite building nearly half of the planned infrastructure network, our findings suggest the built environment is not perceived to be oriented to bicycling. This study provides policy and practice recommendations for developing cycling cities in North America as they transition towards established cycling cities.